Common bean yield due to the application of nitrogenous fertilizers in topdressing (Revista de Ciências Agroveterinárias, 2017)
With the intention to reduce losses of nitrogen (N) resulting from soil fertilization, several modified nitrogen fertilizers are being made available to growers. This study aimed to evaluate the response of common beans to nitrogen fertilizers applied in topdressing. The experiment was conducted in Vacaria, Southern of Brazil, on an Oxisol with 516 g kg-1 clay, pH = 5.2 and 46 g kg-1 organic matter. The experimental area was previously an apple orchard for twenty years. The treatments included the following commercial mineral fertilizers: conventional urea, Super N®, Kimcoat N®, Nitro Mais®, Super Nitro®, Producote®, Sulfammo Meta 29® and ammonium nitrate, all applied at a rate of 60 kg ha-1, in topdressing, in addition to a control without application of N. The availability of N in soil, N in the leaves, protein in the grain, mass of 1,000 grains, and grain yield was evaluated. The average grain yield across treatments was 3,770 kg ha-1 and was not affected by any N fertilizer applied at topdressing. In addition, N fertilizers did not affect any soil and plant evaluated attribute, including N availability in the soil 21 days after application. Thus, soil organic matter supplied all N needed to the plants, mainly due to the good rainfall distribution.
Keywords: urea coated; slow release fertilizers; fertilizer efficiency.